Birth Order Effects on Education: Insights from Low- And Middle-Income Countries - Silvia Mendolia; Olena Stavrunova; Marian Vidal-Fernandez (Institute of Labor Economics (IZA), 2024)
Birth order effects in developed countries are consistently negative. That is, the later a child is born within a family, the worse their adult economic outcomes relative to their earlier-born siblings are. However, studies of birth order effects in emerging countries are scarcer and yield conflicting birth order effect signs. We study whether this divergence in results is due to within-country data idiosyncrasies or methods heterogeneity. We use almost 1.8 million observations gathered from the Demographic and Health Survey (DHS) to measure birth order effects on children's educational outcomes in 35 developing countries, between the mid-1980s and 2020. To the best of our knowledge, this is the first study analysing birth order effects in a comprehensive set of developing countries. In developing countries, families tend to be relatively large and within-family resources scarce. The DHS contains harmonised data and variables for all countries, providing a picture of birth order effects that is consistent across the developing world. Using mothers' fixed effects models, we estimate the impact of birth order on standardised years of schooling and school attendance, exploring non-linearities in birth order effects, as well as heterogeneous effects by gender, socio-economic characteristics and over time. Overall, we find negative birth order effects on educational attainment in 32 out of 35 countries. Consistent with this, we find that the probability of not being in school increases with birth order. We find that in most countries, overall birth order effects do not vary by gender, family wealth, location or over time. In countries where we do find differences in birth order across these dimensions of heterogeneity, the negative birth order effects are stronger for children from poorer households, and households in rural areas.
Keywords: I10; I20; 330; birth order; education; low income countries